Pengaruh ENSO terhadap Curah Hujan Tahunan di Wilayah Urban Balikpapan Berdasarkan Oceanic Niño Indeks Periode 1995–2024 - Valennur, Muhammad Audric; Hidayat, Rafli Akbar; Anargya, Daniswara Alief Aydin; Budiarsa, Anugrah Aditya; Al-ghifari, Najwan (Dept. Marine Science, 2026)
Global climate variability, particularly the El Niño–Southern Oscillation (ENSO), influences rainfall patterns in tropical regions, including Indonesia. Balikpapan City, as a coastal urban area, is highly vulnerable to changes in rainfall, while studies linking the ENSO index to local-scale rainfall remain limited. This study aims to analyze the relationship between ENSO variability and annual rainfall in the urban area of Balikpapan. The data used included annual rainfall from the Sultan Aji Muhammad Sulaiman Sepinggan Class I BMKG Station and the Oceanic Niño Index (ONI) issued by the National Oceanic and Atmospheric Administration (NOAA) during the period 1995–2024. ENSO variability is represented by annual extreme ONI values and analyzed using descriptive statistics and Pearson's correlation. The results show that annual rainfall in Balikpapan City tends to decrease during the El Niño phase and increase during the La Niña phase, although this pattern is not always consistent from year to year. Pearson correlation analysis shows a weak relationship between ENSO and annual rainfall, with a coefficient of determination (R²) value of 0.0365. These findings indicate that ENSO plays a role as one of the factors controlling rainfall variability in Balikpapan City, but it is not the sole dominant factor, so the influence of regional and local climate processes also needs to be considered.